2016
DOI: 10.3847/0004-637x/823/2/143
|View full text |Cite
|
Sign up to set email alerts
|

z ≳ 7 GALAXIES WITH RED SPITZER/IRAC [3.6]–[4.5] COLORS IN THE FULL CANDELS DATA SET: THE BRIGHTEST-KNOWN GALAXIES AT z ∼ 7–9 AND A PROBABLE SPECTROSCOPIC CONFIRMATION AT z = 7.48

Abstract: z 7 galazies with red spitzer/IRAC [3.6]-[4.5] colors in the ≳ full CANDELS data set: the brightest-known galaxies at z 7-∼ 9 and a probable spectroscopic confirmation atz= 7.48Article (Published Version) http://sro.sussex.ac.uk Roberts-Borsani, G W, Bouwens, R J, Oesch, P A, Labbe, I, Smit, R, Illingworth, G D, van Dokkum, P, Holden, B, Gonzalez, V, Stefanon, M, Holwerda, B and Wilkins, S (2016) z 7 ≳ galazies with red spitzer/IRAC [3.6]-[4.5] colors in the full CANDELS data set: the brightestknown galaxie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
267
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(296 citation statements)
references
References 92 publications
(237 reference statements)
29
267
0
Order By: Relevance
“…Indeed, spectroscopic confirmation has recently been obtained for three UV-luminous (M 22 UV~-mag) galaxies at z 7.5 8.7 -with H 25.1 AB selected from CANDELS fields (Roberts-Borsani et al 2016), one at z 8.7 (Zitrin et al 2015) and one at z 11 (GN-z11; Oesch et al 2016). Furthermore, the lower spatial resolution of ground-based observations, compared to HST data, can blend the signal from mergers or from physically unrelated objects and hence make them appear as single sources (e.g., Bowler et al 2017), resulting in an over-estimate of the bright end of the LF and an underestimate of the LF at lower luminosities.…”
Section: = -+mentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, spectroscopic confirmation has recently been obtained for three UV-luminous (M 22 UV~-mag) galaxies at z 7.5 8.7 -with H 25.1 AB selected from CANDELS fields (Roberts-Borsani et al 2016), one at z 8.7 (Zitrin et al 2015) and one at z 11 (GN-z11; Oesch et al 2016). Furthermore, the lower spatial resolution of ground-based observations, compared to HST data, can blend the signal from mergers or from physically unrelated objects and hence make them appear as single sources (e.g., Bowler et al 2017), resulting in an over-estimate of the bright end of the LF and an underestimate of the LF at lower luminosities.…”
Section: = -+mentioning
confidence: 90%
“…Distribution with redshift of the absolute magnitude of the bright LBGs detected so far at z 7  . We include measurements of Oesch et al (2014), Bouwens et al (2015), Roberts-Borsani et al (2016), Calvi et al (2016), Bowler et al (2017), and Ono et al (2017) as indicated by the legend. Our candidate LBGs are marked as red points with error bars and lie at the high-luminosity end of all candidate z 8 LBGs to date.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing possibility is that different physical properties of the H II regions concur in explaining both Lyα visibility and a larger EW([O III]+Hβ) (see also Roberts-Borsani et al 2016;Stark et al 2017). The IRAC color of the Lyα emitting galaxies can thus be explained by these objects being younger and more metal-poor, and thus with harder ionization fields, than nonemitting ones.…”
Section: Discussionmentioning
confidence: 99%
“…The spectral energy distribution of objects in the reionization epoch is affected by emission from [O III] 4959,5007 ll and Hβ at IR wavelengths, resulting in a bluing of the IRAC 3.6-4.5 μm color at z∼6.6-6.9, where the lines affect the 3.6 μm band, and a reddening at z>7 when they enter the 4.5 μm one (Wilkins et al 2013). These signatures yielded evidence of extremely strong line emission in high-z galaxies, and enabled more accurate photometric redshifts and constraints on their specific star formation rate (SSFR; Finkelstein et al 2013;Smit et al 2014Smit et al , 2015Zitrin et al 2015;Roberts-Borsani et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Since we know (in part from SED models) which lines are typically stronger in star-forming young galaxies, we can anticipate the effect of brightening on the broadband photometry at a given redshift. This selection technique is similar in nature to that recently adopted by Smit et al (2014Smit et al ( , 2015 and Roberts-Borsani et al (2016) to successfully search for z ∼ 6 − 8 galaxies with strong rest-frame optical emission lines. For example, all 4 objects at z > 7 predicted by Roberts-Borsani et al (2016) to be prominent emission line galaxies from their unusual broadband colors were later found to exhibit Lyα in follow-up observations (Oesch et al 2015;Stark et al 2015;Zitrin et al 2015c;Roberts-Borsani et al 2016).…”
Section: Introductionmentioning
confidence: 99%